Nanopore Influenza A Virus WGS using one step RT/PCR with RBK barcoding v1 - Tom Williams (2022)
A protocol to generate Influenza A Virus sequences from RNA extracts in under 24 hours with less than two hours of hands on time. Based on: King, J., Harder, T., Beer, M., & Pohlmann, A. (2020). Rapid multiplex MinION nanopore sequencing workflow for Influenza A viruses.BMC Infectious Diseases,20(1). https://doi.org/10.1186/s12879-020-05367-y Zhou, B., Donnelly, M. E., Scholes, D. T., st. George, K., Hatta, M., Kawaoka, Y., & Wentworth, D. E. (2009). Single-Reaction Genomic Amplification Accelerates Sequencing and Vaccine Production for Classical and Swine Origin Human Influenza A Viruses.Journal of Virology,83(19), 10309–10313. https://doi.org/10.1128/jvi.01109-09 Tested with up to 20 RNA extracts from samples per run, alongside: Negative control of nuclease-free water Positive control of H1 Positive control of H3 Positive control of lambda phage, introduced at barcoding stage (i.e. not amplified), as an assessment of barcode crosstalk